Biochemical and nutritional characterization of chickpea (Cicer arietinum) cultivars - KAUR, SARBJIT; KAUR, SATVIR; GUPTA, ANIL K; KAUR, NARINDER; JAVED, M (The Indian Journal of Agricultural Sciences, 2014)
Thirty nationally released chickpea cultivars were evaluated for carbohydrate composition, soluble proteins, total lipids and anti-nutritional factors such as phenolic compounds, tannins, bound fructose of sucrose and raffinose family oligosaccharides, phytic acid, saponins, trypsin inhibitors and activities of enzymes related to them such as acid and alkaline phosphatases and a-galactosidase. Phytic acid showed a lot of diversity between cultivars and varied from 4.74-20.40 mg/g. Avrodhi, BG 256 and Virat were found to be nutritionally important as they had higher protein content (241.5 mg/g–261.5 mg/g) and starch content was found to be between 412.4 mg/g–485.5 mg/g. Avrodhi and BG 256 had lower content of tannin, phytic acid, saponin and trypsin inhibitors and the content of bound fructose of raffinose family oligosaccharides was found to be minimum in Avrodhi. Virat had the highest protein content among kabuli cultivars and it had lower amount of total phenols, flavonols, tannins and phytic acid. HC 1, BG 1053, Pant G 186 and PBG 1 had protein content between 200.0 mg/g–211.5 mg/g and had higher content of tannin, saponin, phytic acid and total phenols. Five cultivars namely HC 3, Vishal, ICCV 10, JG 315 and Saki 9516 had most of the anti-nutritional factors in medium content. Bound fructose of raffinose family oligosaccharides in kabuli cultivars were found to be in the range of 8.31-10.06 mg/g whereas in desi a lot of variation was observed and it ranged from 5.53 mg/g to 10.13 mg/g. All the cultivars were found to cluster in major four groups on the basis of principal component analysis. The result showed the diversity between nutritional and antinutritional factors in the cultivars that could be further used by plant breeders to develop superior genotypes.